Biodiversity of Coleoptera (Insecta) in Central European Russia - Leonid V. Egorov; Aleksey S. Sazhnev; Sergey V. Dedyukhin; Alexander B. Ruchin; Olga S. Trushitsyna; Anna M. Nikolaeva; Mikhail N. Esin; Evgeniy A. Lobachev (Diversity)
(1) Background: Beetles (Insecta: Coleoptera) are the most diverse order of insects. The beetle species live in many ecosystems around the globe and their roles in ecosystems are very diverse; therefore, it is important to know the local and regional biodiversity. Conservation of the entomofauna in individual macroregions requires effort to study the distribution and abundance of insects. To this end, databases are being created to record this information so that the status of a species can be objectively assessed and, if necessary, measures taken to protect it. (2) Methods: The materials were collected from the territory of eleven regions of European Russia (Ryazan, Tambov, Penza, Voronezh, Lipetsk, Moscow (including the city of Moscow), Vladimir, Kursk, Tula and Kaluga Oblasts and the Republic of Mordovia), mainly during the last approximately 20 years (2005–2024). The beetles were collected by different means (manual collection; the use of soil traps, fermental crown traps, and Malaise traps; light fishing; sweeping with an entomological net on plants and under water, etc.). (3) Results: The dataset presents data on 1310 species and subspecies of Coleoptera from 74 families found in the Eastern Part of the Eastern European Plain. In total, there are 65,100 samples and 10,771 occurrences in the dataset. (4) Conclusions: The largest families in terms of species diversity are Curculionidae (198 species), Carabidae (183 species), Staphylinidae (121 species) and Chrysomelidae (120 species).